The effects of taurine on Ca2+ uptake by the sarcoplasmic reticulum and Ca2+ sensitivity of chemically skinned rat heart. - Steele, D S (1990)
1. Caffeine (10 mM) induced a transient contracture in saponin-treated cardiac trabeculae as a result of Ca2+ release from the sarcoplasmic reticulum (SR). Regular cycles of uptake and release were repeated to stabilize responses. The SR accumulated Ca2+ during the period prior to the addition of caffeine and this was reflected in the size of the caffeine contracture. Increasing the time for Ca2+ loading between successive caffeine exposures resulted in an increase in the amplitude of the contracture. Similarly, the size of the contracture was a function of the calcium ion concentration [( Ca2+]) in the preceding loading period. 2. Taurine (microM-40-mM), when included in both loading and caffeine solutions, markedly potentiated the caffeine-induced contracture. The effect occurs even if taurine was included only in the loading solutions. The potentiating effect was ascribed to a direct action of taurine on the SR, since taurine did not significantly change the [Ca2+] in the loading solutions. 3. The maximal effect of taurine was produced at approximately 5 mM; higher taurine concentrations caused a lesser potentiation of the caffeine contracture. If the solutions were balanced with respect to osmolarity the effect of taurine did not decline at high concentrations. 4. If the [Ca2+] in the loading solutions was increased to produce a caffeine-induced contracture that peaked close to maximal Ca2(+)-activated force, taurine caused a fall in the size of contracture and a more variable response. This result could be explained by an increase in the spontaneous release of Ca2+ from the SR in the presence of taurine. 5. In Triton-skinned trabeculae, taurine (1 mM-40 mM) increased the Ca2+ sensitivity of the contractile proteins in a dose-dependent manner but had little effect on maximum Ca2(+)-activated force. The increase in Ca2+ sensitivity was small: in a typical experiment 30 mM-taurine reduced the [Ca2+] necessary for half-maximal activation from 3.02 to 2.56 microM, with no significant change in the shape of the relationship.